Penerapan (Re)kontruksi Akuntansi Keuangan Bagi Hasil Sistem Mato Pada RMP Terang Bulan - Sartika, Dewi; Mulyani, Fitrah; Ilyas, Andre (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This research aims to apply (re)construction of the Mato System Profit Sharing Financial Accounting (AKBHSM) at Padang Restaurant (RMP) Terang Bulan and to determine the obstacles faced in implementing (re)construction of AKBHSM at RMP Terang Bulan. In this research the author will apply the research results of Hanif (2017) which produces a new concept in the form of AKBHSM Reconstruction which is the result of the synergy of the binary opposition of "Eastern" accounting (AKBHSM) and "Western" accounting. The data collection methods that the author used in this research were participant observation, interviews, and documentation. In implementing AKBHSM reconstruction, the "depreciation expense" account is an adjustment to production assets that are charged as production costs (part of Work In Process). The fixed assets owned are one of the production assets, so adjustments are needed so that they can be charged as production costs. The implementation of AKBHSM reconstruction at RMP Terang Bulan for retained profit sharing does not use a percentage but is set aside every day in the amount of IDR 100,000.-. By no longer having "renewal fund allocation debt" the investor capital invested will not decrease so that the capital can reflect the investor's ownership and rights in the truest sense through a "mato system-based business legal entity". In modern accounting, net profit/loss will appear in the financial position report, but in the AKBHSM reconstruction concept what appears is "retained profit sharing". This is because after the profit and loss report is prepared, the profit sharing system results in a net profit ready to be shared. The financial reports prepared refer to SAK EMKM with the AKBHSM reconstruction concept approach developed by Hanif (2017), while the reports prepared are mato system profit sharing reports, financial position reports and notes to financial reports.